2021
DOI: 10.3390/ijgi10040243
|View full text |Cite
|
Sign up to set email alerts
|

The Soil Nutrient Digital Mapping for Precision Agriculture Cases in the Trans-Ural Steppe Zone of Russia Using Topographic Attributes

Abstract: Topographic features of territory have a significant impact on the spatial distribution of soil properties. This research is focused on digital soil mapping (DSM) of main agrochemical soil properties—values of soil organic carbon (SOC), nitrogen, potassium, calcium, magnesium, sodium, phosphorus, pH, and thickness of the humus-accumulative (AB) horizon of arable lands in the Trans-Ural steppe zone (Republic of Bashkortostan, Russia). The methods of multiple linear regression (MLR) and support vector machine (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 54 publications
1
17
0
2
Order By: Relevance
“…MrRTF showed a correlation of −0.21 with SOM, −0.06 with CEC. Suleymanov et al (2021) [33] reported 0.5 correlation between SOM and MrRTF and MrRTF was a key attribute for mapping soil organic carbon and thickness of humus. Ref.…”
Section: Spatial Trend Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…MrRTF showed a correlation of −0.21 with SOM, −0.06 with CEC. Suleymanov et al (2021) [33] reported 0.5 correlation between SOM and MrRTF and MrRTF was a key attribute for mapping soil organic carbon and thickness of humus. Ref.…”
Section: Spatial Trend Modelingmentioning
confidence: 99%
“…It is possible to generate many terrain attributes from a DEM, but it is important to limit their number to avoid redundancy, model overfitting and interpretations [32]. Suleymanov et al (2021) [33] found that of 17 generated terrain attributes, only three of them (elevation, slope, and MrRTF) were most important for predicting the spatial variability of soil properties including SOM. We focused on those terrain attributes that have a close relationship to water redistribution across a post-glaciated landscape such as at ACRE and that are commonly used in DSM.…”
Section: Terrain Attributesmentioning
confidence: 99%
“…Nevertheless, the bare soil, especially after opencast mining, is known as lacking plant nutrients, aggregation, and organic matter, which make the revegetation process difficult [4,5]. Monitoring the areas, especially in a chronosequence study, is therefore necessary to understand whether the adopted rehabilitation practices are contributing to the improvement of soil attributes and the rehabilitation of the disturbed area [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…One promising technique for rehabilitation monitoring is the use of digital image processing of remote sensing data for assessing long-to short-term landscape dynamics. In addition, it can estimate important indicators of soil quality in a cost-effective and rapid manner when compared with repeated field surveys and laboratory measurements in large areas with difficult access [7,8]. One example is the correlation between spectral indices (i.e., normalized difference vegetation index (NDVI) and bare soil index (BSI)) and soil properties such as organic carbon, nutrients, and texture [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…В мировой практике методы цифрового картографирования эффективно используются для картографирования классов и свойств почв на основе экологических ковариат, рассчитываемых по данным дистанционного зондирования Земли Soil organic…, 2018;Suleymanov et al, 2021). Однако такой метод не подходит для крупномасштабного картографирования, когда расстояние между точками отбора проб почвы слишком мало и измеряется в сантиметрах, и при этом отсутствуют подробные данные дистанционного зондирования экологических ковариат с высоким пространственным разрешением.…”
unclassified